The Impact of Load Unbalance on Neutral Conductors Losses and Transformer Efficiency - Widagdo, Reza Sarwo; Prenata, Giovanni Dimas; Rafli, Syah Achmad Amar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The transformer is a crucial component in the electrical energy distribution system. Therefore, strict supervision is necessary to ensure that the electricity supply network is maintained and safe during operational processes. This research aims to measure the transformer load installed at PT. Sunrise Steel to determine the values of loading, imbalance, power losses, and efficiency of the loaded transformers. This measurement is important to ensure that the values resulting from operational processes do not exceed predetermined limits. Observations over 10 days show that the peak load value during operational time is 66.08%, which can still be categorized as quite good. The load imbalance reached a maximum value of 10.13%, which is categorized as poor since SPLN regulations state that a good imbalance should be below 10%. The percentage of power loss has a maximum value of 0.33%, and the best transformer efficiency reaches 97.17%, which is the highest efficiency value considering several other loss parameters.